Mycetoma in Iran: Causative agents and geographic distribution - Shahindokht Bassiri-Jahromi (Wolters Kluwer Medknow Publications, 2014)
Background: Mycetoma is a chronic granulomatous disease caused by true fungi (eumycetoma) or filamentous bacteria (actinomycetoma). It usually involves the subcutaneous tissue after a traumatic inoculation of the causative organism. We reviewed retrospectively 13 patients with mycetoma. Materials and Methods: This study reports the etiologic agents and distribution of mycetoma in 35 cases from 1994 to2009 in Iran. The diagnostic of mycetoma were confirmed by histopathology and direct preparation, culture techniques, and histopathology of granules and surgical biopsies, radiological examination of the affected site. Results: Mycetoma was identified in 35 patients of 168 suspected patients (20.8%). They occurred in 22 male and 13 females. Their ages ranged from 14 to 80 years. The duration of the disease ranged from two months to 38 years. Sixteen patients had eumycetoma, and 19 patients had actinomycetoma, one of them had mix infections by eumycetoma and actinomycetoma. The majority of the patients were from central and states in south and north of Iran. The feet were most affected site (65.7%) of the cases, followed by hands (25.7%), face (2.8%), and trunk (2.8%), and buttock (2.8%). Most patients (68.5%) were more than 40 year-old. The male to female ratio was 5:3. The disease was abundant among housewife in urban and farmer in rural area of Iran. The most common prevalent mycetoma agents in this study were Actinomyces sp. There was a history of risk factors in 28.6% of patients in this study. Conclusion: Mycetoma occasionally occurs particularly in the South, Central, and North of Iran, and seen most often in persons, who live in hot, humid climates. If there are risk factors for invasive fungal infections traumatic inoculation with any fungus may result in rapid local spread and systemic disease, often with fatal outcome.